Empirical analysis on emerging issues of Malaysia outward FDI from macroeconomic perspective - Kueh, Jerome Swee Hui; Puah, Chin-Hong; Shazali, Abu Mansor (Universiti Malaysia Sarawak (UNIMAS), 2007)
The evidence of Malaysia outward FDI has become obvious particularly in the 1990s. Despite remain as the preference of FDI destinations, Malaysia also emerged as the fifth largest investor among the developing economies in Asia region (UNCTAD, 2005). In view of that, this study intends to examine the macroeconomic determinants of outward FDI of Malaysia, namely real income, exchange rate, trade openness and interest rate. The Johansen and Juselius cointegration test and the vector error correction model are utilized in this study to analyze the quarterly data from 1991:Q1 to 2005:Q4. We found that outward FDI of Malaysia is positively affected by all the variables under study in long run. However, the interest rate does not Granger cause outward FDI in the short run.